Locally advanced rectal cancer patients with mismatch repair protein deficiency can obtain better pathological response after regional chemoembolization - Gao, Yuchen; Xiao, Hualiang; Meng, Wenjun; Liao, Juan; Chen, Qi; Zhao, Guowei; Li, Chunxue; Bai, Lian (Frontiers in Oncology, 2023)
Background and objective Preoperative transcatheter rectal arterial chemoembolization (TRACE) can enhance the pathological response rate in some patients with locally advanced rectal cancer (LARC). However, how to accurately identify patients who can benefit from this neoadjuvant modality therapy remains to be further studied. Deficient mismatch repair (dMMR) protein plays a crucial role in maintaining genome stability. A proportion of patients with rectal cancer are caused by the loss of mismatch repair (MMR) protein. Given the role of MMR in guiding the efficacy in patients with colorectal carcinoma (CRC), this study is designed to evaluate the effect of dMMR status on the response to neoadjuvant therapy through a retrospective analysis. Methods We launched a retrospective study. First, we selected patients with LARC from the database, and these patients had received preoperative TRACE combined with concurrent chemoradiotherapy. Then, the tumor tissue biopsied by colonoscopy before intervention was taken for immunohistochemistry. According to the expression of MLH-1, MSH-2, MSH-6 and PMS-2, these patients were divided into dMMR protein group and proficient MMR (pMMR) protein group. All patients underwent pathological examination at the end of neoadjuvant therapy, either surgically excised tissue or colonoscopically biopsied tissue. The end point was the pathologic complete response (pCR) after TRACE combined with concurrent chemoradiotherapy. Results From January 2013 to January 2021, a total of 82 patients with LARC received preoperative TRACE combined with concurrent chemoradiotherapy, and the treatment was well tolerated. Among 82 patients, there were 42 patients in the pMMR group and 40 patients in the dMMR group. 69 patients returned to the hospital for radical resection. In 8 patients, the colonoscopy showed good tumor regression grade after 4 weeks of interventional therapy and refused surgery. The remaining five patients were neither surgically treated nor reexamined by colonoscopy. 77 patients were eventually enrolled in the study. Individually, the pCR rates of these two groups (10%, 4/40 vs. 43%, 16/37) showed significant difference (P < 0.05). Biomarker analysis indicated that patients with dMMR protein had a better propensity for pCR. Conclusion In patients with LARC, preoperative TRACE combined with concurrent chemoradiotherapy showed good pCR rates, especially in patients with dMMR. Patients with MMR protein defects have a better propensity for pCR.